Long-term changes in aerosol radiative properties over Ny-Ålesund: Results from Indian scientific expeditions to the Arctic - Gogoi, Mukunda M.; Pandey, Santosh K.; Arun, B.S.; Nair, Vijayakumar S.; Thakur, Roseline C.; Chaubey, Jai Prakash; Tiwari, Anoop; Manoj, M.R.; Kompalli, Sobhan Kumar; Vaishya, Aditya; Prijith, S.S.; Hegde, Prashant; et al. (Polar Science, 2021)
Continuous long-term monitoring of black carbon (BC) mass concentration and aerosol light scattering coefficient (σSCA), supplemented by number size distribution and chemical composition, are utilized in this study to understand the temporal changes in aerosol properties, associated source processes and radiative effects at Ny-Ålesund (79 oN) in the Svalbard Archipelago. A statistically significant decreasing trend in BC (- 24.7 ng m−3 decade−1) is observed during spring of 2010–2019. In contrast, σSCA depicted a general increasing trend (5.2 Mm−1 decade−1) during 2011–2016. BC and σSCA were higher during winter and spring. Aerosol single scattering albedo was highest in May ~ 0.95 (during spring) and lowest in September ~ 0.87 (during summer). Fractional share of BC to total aerosol mass was higher in winter and summer. Anthropogenic SO42− and NO3− (after ssNa+) species dominated the summer, when total number and mass concentrations of aerosols were at their minimum. Elemental Carbon (EC) and Organic Carbon (OC) showed higher concentrations in spring with EC-to-OC ratio ~ 0.08 - 0.22. The columnar AOD varied between 0.01 and 0.20 (annual mean ~ 0.09), resulting in aerosol radiative forcing (in the top of the atmosphere) ~ 0.15 - 2.69 Wm-2 in the month of April (during spring). Potential source contribution function (PSCF) revealed the dominant source areas to be over Europe and Russia in terms of contributing to the seasonal high BC mass concentrations at Ny-Ålesund. Our study has also revealed an unusual impact of biomass burning aerosols (advected from the Alaska wildfire) during July 2015. journal article